Occupational health management of work-related stress: guidelines versus practice. (30th April 2021) - Palka, G; Sen, D
Abstract: Background: Work-related stress, anxiety and depression (WRSAD) are common, overlapping mental health problems burdened with major medical, occupational, institutional and societal implications. Current occupational health (OH) management of WRSAD is based on clinical and managerial guidelines and individual risk assessment. Aims: The study sought to identify patterns of OH advice in WRSAD and the relationships between the OH advice, available evidence, experience and expertise of the OH doctors (OHDs). Methods: A retrospective cross-sectional analysis of 101 first-time OH consultations for WRSAD by nine OHDs. Results: The three most common OH interventions included follow-up OH consultations, adjusted duties and referrals for counselling. All OHDs preferred a light-touch approach but the less experienced and qualified OHDs were more proactive and prescriptive. Conclusions: In the absence of a specific occupational medical guideline for the management of WRSAD, the OH interventions may be guided by clinical guidelines, individual risk assessment, the client's circumstances or the experience, expertise and preferences of the OHDs. In the study group, OH interventions were under-utilized and not consistently applied. Our findings support the argument for OH guideline for WRSAD to improve the consistency and effectiveness of OH interventions. This is important given the scale of the problem and the recent increase in WRSAD during the COVID-19 pandemic.